Cops, drugs and interloping academics: an ethnographic exploration of the possibility of policing drugs differently in South Africa. (3rd July 2016) - Marks, Monique; Howell, Simon
Abstract: This article presents an ethnographic exploration of the policing of illegal substances in a city in South Africa. Situated contextually, we show how specific illegal drug policing practices are reinforced both institutionally and in the daily practices and activities of law enforcement officials. We explore the tension resulting from the demand for police officers to enforce punitive forms of regulation, despite their own awareness of the ineffectiveness of such strategies. Drawing on the experiences of the officers we engaged with, we show that policing aimed more at harm reduction than tough enforcement is possible. This, we argue, is the result of shifts in the structural field of policing (particularly at the policy level) and contradictions in the basic assumptions that police officers have about drug users, drug markets and what constitutes 'real' police work.